XPS study of the adsorption mechanisms of DNA onto polypyrrole particles. Issue 4 (2004) - Saoudi Saoudi, Bachir Bachir; Jammul Jammul, Noraldeen Noraldeen; Chehimi Chehimi, Mohamed M. Mohamed M.; Jaubert Jaubert, Anne-Sophie Anne-Sophie; Arkam Arkam, Chakib Chakib; Delamar Delamar, Michel Michel
Abstract : DNA adsorption onto polypyrrole (PPy) powder particles has been monitored, ex situ, by X-ray photoelectron spectroscopy (XPS) technique. DNA adsorption isotherms were determined by the quantitative analysis of the XPS spectra, and by plotting the X/N atomic ratios (X = C, O, Cl, P and Na) versus DNA equilibrium concentration. All XPS isotherms are of high affinity type, showing high adsorption amounts at low DNA concentrations in the suspension. Moreover, inspection of the C1s peak structure of the PPy–DNA complex revealed that it gradually gets wider and less tailing as DNA adsorbs, clearly showing the DNA contribution to the peak enlargement. In addition, the changes observed in the Cl2p structure bring a strong supporting evidence of anion-exchange mechanism that takes place at initial stages of the interaction. Actually, the polypyrrole backbone loses part of its residual chlorides as the first DNA fragments adsorb and neutralize the PPy positive charges at the interface. Moreover, at relatively high amounts of adsorbed DNA, the PPy surface becomes screened necessitating thus that sodium cations co-adsorb in order to compensate for the excess of DNA negative charges. As a consequence of such screening of the PPy surface, DNA adsorption results in a positive spectral shift of all peaks of approximately 2.0 eV, a value that leads to the conclusion that DNA partially covers the PPy.